Comparative genomic analysis of Myroides odoratimimus isolates. Issue 2 (23rd May 2018) - Hu, Shaohua; Cao, Lin; Wu, Yiyin; Zhou, Yajun; Jiang, Tao; Wang, Liqiang; Wang, Qiujing; Ming, Desong; Chen, Shicheng; Wang, Mingxi
Abstract: Myroides odoratimimus is an important nosocomial pathogen. Management of M. odoratimimus infection is difficult owing to the multidrug resistance and the unknown pathogenesis mechanisms. Based on our previous genomic sequencing data of M. odoratimimus PR63039 (isolated from a patient with the urinary tract infection), in this study, we further performed comparative genomic analysis for 10 selected Myroides strains. Our results showed that these Myroides genome contexts were very similar and phylogenetically related. Various prophages were identified in the four clinical isolate genomes, which possibly contributed to the genome evolution among the Myroides strains. CRISPR elements were only detected in the two clinical (PR63039 and CCUG10230) isolates and two environmental (CCUG12700 and H1bi) strains. With more stringent cutoff parameters in CARD analysis, the four clinical M. odoratimimus contained roughly equal antibiotic resistance genes, indicating their similar antibiotic resistance profiles. The three clinical (CCUG10230, CCUG12901, CIP101113) and three environmental (CCUG12700, L41, H1bi) M. odoratimimus strains were speculated to carry the indistinguishable virulent factors (VFs), which may involve in the similar pathogenesis mechanism. Moreover, some VFs might confer to the high capacity of dissemination, attacking tissue cells and induction of autoimmune complications. Our results facilitate the research of antibiotic resistance and the development of therapeutic regimens for the M. odoratimimus infections. Abstract : We reported the comparative genomic analysis of 10 Myroides Odoratimimus isolates. We clarified the similarities and differences among these strains, the mechanisms of antibiotics resistance and pathogenicity.